The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.4314/jasem.v25i2.21
|View full text |Cite
|
Sign up to set email alerts
|

Unresolved Water Conflicts by Water Sector Institutions in Ewaso Ng’iro North River Sub-Basin, Kenya

Abstract: Water conflicts have huge impacts on livelihoods and without proper redress, have capacity to stall economic development of a community. This paper therefore explicates the impacts of unresolved water related conflicts in Ewaso Ng’iro North River sub-basin in Kenya and their persistence despite past major institutional and policy reforms in the water sector. Repetitive unresolved water conflicts curtail the prosperity of the communities on river basins. Study  objective was to assess continued unresolved confl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 26 publications
0
1
0
Order By: Relevance
“…The sub-catchment receives an average annual rainfall of 400mm, is a water-stressed region, and while there are few perennial streams, the River Loisukut, formerly known as the Sinyai River, flows around 93 kilometers and is the sub-catchment's main source of water (Lesrima, 2019).…”
Section: Main Sources Of Watermentioning
confidence: 99%
“…The sub-catchment receives an average annual rainfall of 400mm, is a water-stressed region, and while there are few perennial streams, the River Loisukut, formerly known as the Sinyai River, flows around 93 kilometers and is the sub-catchment's main source of water (Lesrima, 2019).…”
Section: Main Sources Of Watermentioning
confidence: 99%
“…These challenges can relate to a lack of collective action due to the individualistic nature of the communities they represent. In addition to the lack of collective actions by the communities, studies have shown that climate change, 190 rapid changes in land-use systems, and societal changes such as population increase, constantly challenge the ability of WRUAs to modify rules for water allocation (Dell'Angelo et al, 2014;Lesrima, 2019;Aarts, 2012).…”
Section: Case Study Areamentioning
confidence: 99%
“…This is because they face pressure from other pastoralists who immigrate from far 425 downstream in search of water and pasture while their upward emigration faces inflexible resistance from the agricultural communities in the upslopes. This can explain the manifestation of fatal seasonal conflicts observed between upstream and downstream communities in the Upper Ewaso Ng'iro catchment (Lesrima, 2019;Kiteme, 2020). Within the game environment, higher profits were realized towards the final rounds when the boardgame system was relatively stable.…”
Section: Decisions Made During Gameplaymentioning
confidence: 99%
“…WRUA manage specific water sheds with the main role of monitoring water use and curbing misuse. Despite this, a large amount of water is extracted for irrigation in the up and midstream region, leaving little or no water for downstream communities, often leading to water-related conflicts (Kiteme, 2020;Lesrima et al, 2021).…”
Section: Application Of Kilimo Na Maji: Results From Two Games Sessionsmentioning
confidence: 99%
“…Downstream communities were perceived to be neutral on most of the crops, including those with a high-water requirement. This was an unexpected result, since there is documented evidence of persistent water-related conflicts between pastoralists in the downstream and crop farmers in the upstream, originating from what downstream communities consider as excessive irrigation in the upstream region Kiteme, 2020;Lesrima et al, 2021;Mutiga et al, 2010). This could mean that although farmers were aware of the downstream communities' preferences, this awareness yielded to the need to please other reference groups.…”
Section: Farmers' Perceived Preferences Of Reference Groupsmentioning
confidence: 98%